Falls in older persons with intellectual disabilities: fall rate, circumstances and consequences. (29th October 2012) - Smulders, E.; Enkelaar, L.; Weerdesteyn, V.; Geurts, A. C. H.; van, H.
Abstract Background Falling is a common cause of injuries and reduced quality of life. Persons with intellectual disabilities (ID) are at increased risk for falls and related injuries. As the number of elderly persons with ID is growing rapidly, it is imperative to gain insight into the quantity of the problem of falling, the circumstances that precipitate falls and to better understand their aetiology in persons with ID. This is the first study to prospectively investigate fall rate, circumstances and fall consequences in older adults with mild to moderate ID. Method Eighty‐two individuals with mild to moderate ID, 50 years and over [mean age 62.3 (SD = 7.6), 34 male], participated in this study, which was conducted at three service providers for persons with ID in the Netherlands. Falls were registered for 1 year with monthly fall registration calendars to determine the fall rate (mean number of falls per person per year). Information on fall circumstances and consequences was obtained from questionnaires completed by caregivers and study participants after each fall. Results We determined that the fall rate in this sample was 1.00 fall per person per year. Thirty‐seven participants reported at least one fall (range 1–6). Sex and age were not related to falls. Most falls occurred while walking (63.3%), outside (61.7%) and in familiar environments (88.9%). Importantly, 11.5% of falls resulted in severe injuries, approximately half of which were fractures. Conclusion The circumstances and consequences of falls in persons with ID are comparable to those of the general elderly population, but the rate is substantially higher. As such, appropriate fall prevention strategies must be developed for individuals with ID.